Legal Protection for Workers Experiencing Unilateral Wages Cuts by Companies Due to the Covid-19 Pandemic - Allena Marvelia Silalahi (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
One of the issues that is currently surfacing is companies cutting workers' wages due to the Covid-19 pandemic. Actual wage deductions can be made in labor or wage regulations if they are based on: In accordance with the agreement between the employer and the worker and of course the applicable legal provisions. However, it is also true that many companies are cutting wages without workers' consent due to poor business conditions exacerbated by the pandemic. The survey method used in this research is a prescriptive law survey method, namely a survey that uses secondary information sources based on positive law in the field of employment as the main source of information. In the case that occurred at PT Y Bandung City, the company failed to fulfill the requirements and obligations to workers/laborers due to unilateral wage deductions. The way to reduce worker/labour wages during the Covid-19 pandemic was supposed to be with an agreement between the company and workers/labourers and it turned out that PT Y Bandung did not fulfill what was required of Law No.13. Mandate related to employment and Sekda No. 3 of 2020 mentions cutting wages during the Covid-19 pandemic and must be in line with the company's agreement.